Investigacion de escenarios de inversion para el optimo mantenimiento de la red vial Estrategica principal de las carreteras de asfalto, lastre y tierra correpondiente a los cantones Atahualpa, piñas Las Lajas, chilla, Portovelo, Zaruma, Balsas y Marcabelí de la provincia de el Oro - Lojan Alburquerque, Jose Lenin (2015)
The need for research investment scenarios achieve identify the best strategies for conservation and maintenance on the main strategic road network of asphalt roads, gravel and dirt of the corresponding to the cantons of the Province Atahualpa, Pineapples, Las Lajas road network, Chilla, Portovelo Zaruma, Balsas, Marcabeli of the province of El Oro. the objective set is to develop a strategic plan for the conservation and road maintenance for the next 20 years. Research and analysis was developed using literature media, web media, field visits and using an optimization engine frontline solver (demo) in Ms- Excel to develop a system of decision-making. The investment plan for roads of the main strategic road network of the aforementioned cantons of the province of El Oro, serve as an example for other provinces and / or municipalities wishing to develop a system of management of public infrastructure assets. Scenario analysis identified the best way to use scarce resources of the provincial government in order to preserve the road network in acceptable condition according to the technical design criteria. Optimizations generated investment scenarios asphalt roads of a sample of 70.5 Km about $ 2, 000,000 are required for the first year and then US $ 1,500,000 per year after achieving bring the road network to a state of good condition. The ballast 220.1 km require a maximum average of US $ 5,000,000 per year to maintain the roads in top condition during the first subsequent years mind less budget is required.